2020
DOI: 10.1088/1751-8121/abbd1a
|View full text |Cite
|
Sign up to set email alerts
|

Exact solution of the position-dependent effective mass and angular frequency Schrödinger equation: harmonic oscillator model with quantized confinement parameter

Abstract: We present an exact solution of a confined model of the non-relativistic quantum harmonic oscillator, where the effective mass and the angular frequency are dependent on the position. The free Hamiltonian of the proposed model has the form of the BenDaniel-Duke kinetic energy operator. The position-dependency of the mass and the angular frequency is such that the homogeneous nature of the harmonic oscillator force constant k and hence the regular harmonic oscillator potential is preserved. As a consequence the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…We conclude that the results of Ref. [1] can be derived by a PCT applied to the constantmass Schrödinger equation for the Rosen-Morse II potential with B = 0 and any A = l = 2, 3, . .…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…We conclude that the results of Ref. [1] can be derived by a PCT applied to the constantmass Schrödinger equation for the Rosen-Morse II potential with B = 0 and any A = l = 2, 3, . .…”
mentioning
confidence: 52%
“…In conclusion, we have shown that the confined harmonic oscillator with positiondependent mass and angular frequency of Ref. [1] can be extended to the case where the confinement parameter is not quantized, its spectrum remaining finite, non-equidistant, and dependent on the confinement parameter. A further extension to a confined shifted harmonic oscillator with similar characteristics has also been constructed.…”
mentioning
confidence: 76%
“…Before presenting the main theorem, we have a lemma with two transformation formulas (which appeared already in [11], but were not derived there).…”
Section: Direct Limit Relation Between Pseudo-jacobi and Hermite Poly...mentioning
confidence: 99%
“…One of the most powerful techniques for such a purpose consists in applying a point canonical transformation (PCT) to an exactly solvable constant-mass Schrödinger equation [21,22]. Recently, such an approach has proved its efficiency again by providing a straightforward generalization [23] of a harmonic oscillator model wherein both the mass and the angular frequency are dependent on the position [24].…”
Section: Introductionmentioning
confidence: 99%